Modulation of the oxidative plasmatic state in gastroesophageal reflux disease with the addition of rich water molecular hydrogen: A new biological vision. Issue 5 (7th March 2018) - Franceschelli, Sara; Gatta, Daniela Maria Pia; Pesce, Mirko; Ferrone, Alessio; Di Martino, Giuseppe; Di Nicola, Marta; De Lutiis, Maria Anna; Vitacolonna, Ester; Patruno, Antonia; Grilli, Alfredo; Felaco, Mario; Speranza, Lorenza
Abstract: Gastroesophageal reflux disease (GERD), a clinical condition characterized by reflux of gastroduodenal contents in the oesophagus, has proved to demonstrate a strong link between oxidative stress and the development of GERD. Proton pump inhibitors (PPIs) have been universally accepted as first‐line therapy for management of GERD. The potential benefits of electrolysed reduced water (ERW), rich in molecular hydrogen, in improving symptoms and systemic oxidative stress associated with GERD was assessed. The study was performed on 84 GERD patients undergoing control treatment (PPI + tap water) or experimental treatment (PPI + ERW) for 3 months. These patients were subjected to the GERD‐Health Related Quality of Life Questionnaire as well as derivatives reactive oxigen metabolites (d‐ROMs) test, biological antioxidant potential (BAP) test, superoxide anion, nitric oxide and malondialdehyde assays, which were all performed as a proxy for the oxidative/nitrosative stress and the antioxidant potential status. Spearman's correlation coefficient was used to evaluate the correlation between scores and laboratory parameters. Overall results demonstrated that an optimal oxidative balance can be restored and GERD symptoms can be reduced rapidly via the integration of ERW in GERD patients. The relative variation of heartburn and regurgitation score was significantly correlated with laboratory parameters. Thus, in the selected patients, combination treatment with PPI and ERW improves the cellular redox state leading to the improvement of the quality of life as demonstrated by the correlation analysis between laboratory parameters and GERD symptoms.